Product recalls: The effects of industry, recall strategy and hazard, on shareholder wealth - Michael Bernon; Marko Bastl; Wenqian Zhang; Mark Johnson (International Journal of Business Science & Applied Management (IJBSAM), 2018)
The purpose of this paper is to provide insights into the effects of product recalls on shareholder wealth of manufacturing firms in different supply chains. Previous research examining this phenomenon is largely uni-sectorial and/or does not consider the interplay of hazard, recall strategy and sector. By utilizing the event study method, this study examines investors' reactions to key product recall characteristics: industry, recall strategy and hazard level, on a cross-industry sample of 296 product recall announcements. The results show a significant negative reaction of share values to product recalls and significant differences between industry type and hazard levels. More regulated and stringent supply chains, such as the automotive and pharmaceutical, showed statistically significant losses in share price. The results show that industry sector and level of hazard associated with defective products are significant factors impacting the shareholder wealth of manufacturing firms. Contrary to some studies, the impact of recall strategy was not confirmed, although proactive recall strategies led, in some cases, to an increase in share price. Further research would benefit from more detailed investigation of recall strategies on the value of companies in specific sectors, particularly ones which are susceptible to frequent and costly product recalls.
Keywords: 650; product recall; cross-industry sector; shareholder wealth; event study; product hazard; recall strategy; reverse logistics